2018
DOI: 10.1016/j.jbusres.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating organisational creativity with theatrical improvisation

Abstract: Although organisational creativity has become an increasingly important performance driver, little is known about how it can be built and stimulated. The existing literature has mostly focused on techniques for improving idea generation in specific and occasional problem-solving situations. However, there is scarce research about how to improve creativity as a quality that pervades everyday operations throughout an organisation. This study explores how theatrical improvisation could foster organisational creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
(55 reference statements)
0
26
0
3
Order By: Relevance
“…One stream has examined the impact of improvisation training. Its findings suggest that OI can enhance employees’ feelings of confidence and abilities to handle unique situations (Daly, Grove, Dorsch, & Fisk, 2009), the development of an entrepreneurial mindset (Balachandra, 2019), and sometimes fostering of organizational creativity (Nisula & Kianto, 2018). A pair of studies using healthcare settings highlight an important ambiguity: One study found that relying on improvisation can lead to disenchantment (Rieder, 2017), whereas the other found it can lead to resilience (Muyinda & Mugisha, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…One stream has examined the impact of improvisation training. Its findings suggest that OI can enhance employees’ feelings of confidence and abilities to handle unique situations (Daly, Grove, Dorsch, & Fisk, 2009), the development of an entrepreneurial mindset (Balachandra, 2019), and sometimes fostering of organizational creativity (Nisula & Kianto, 2018). A pair of studies using healthcare settings highlight an important ambiguity: One study found that relying on improvisation can lead to disenchantment (Rieder, 2017), whereas the other found it can lead to resilience (Muyinda & Mugisha, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Creativity is considered as the vehicle of human self-expression (Paul and Kaufman, 2014). A person with high intrinsic creativity is able to draw on their own ideas and intuitions to imagine, and then produce, novel and useful outcomes (Csikszentmihalyi, 2013; Nisula and Kianto, 2018). Creativity is understood to involve three ways of thinking: generation of new ideas and connections between them, analytical or critical thinking and practical ability (Sternberg and Williams, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Art is also recognised as a tool for generating creativity and innovation in business contexts (Berthoin Antal and Strauß, 2014; Styhre and Eriksson, 2008; Van Den Broeck et al, 2008). For example, training in artistic improvisation stimulated creativity in businesspeople by breaking down individual barriers and increasing openness to novelty (Nisula and Kianto, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…So, it was a synchronized thing between the three of us, with (second first officer) still being able to do all his communications. So that’s how we operated the airplane, and that’s how we got it on the ground .” This might represent an instance of rare and true group improvisation as experienced by musicians or theater actors “in the spirit of shared leadership, responsibility, mutual support, and care” ( Nisula and Kianto, 2018 , p. 485). Indeed, through verbal and nonverbal interactions, the crew coordinated and synchronized their actions in a spontaneous, unplanned, and never experienced way.…”
Section: Creativity Under the Gun: Evidence Of Creativity In High Rismentioning
confidence: 99%